Democracy, Populism and Hyperinflation[s]: Evidence from Latin America - Manoel Bittencourt (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
We test for the populist view of inflation in Latin America between 1970 and 2007. The empirical results - based on the relatively novel panel time-series data and analysis - confirm the theoretical prediction that recently elected governments coming into power after periods of political dictatorship, and which are faced with high economic inequality, end up generating high inflation and macroeconomic instability. All in all, we suggest that the implementation of democracy as such requires not only the 'right political context' - or an appropriately constrained executive - to work well, but it also must come with certain economic institutions (e.g. central bank independence and a credible and responsible fiscal authority), institutions which would raise the costs of pursuing populist policies in the first place.
Keywords: E31; E65; N16; O23; O54; 330; Polarisation; populism; hyperinflation; Latin America.